HCM 2010 : highway capacity manual. (Transportation Research Board, 2010)
"HCM2010, which updates HCM2000, will significantly enhance how engineers and planners assess the traffic and environmental effects of highway projects by: providing an integrated multimodal approach to the analysis and evaluation of urban streets from the points of view of automobile drivers, transit passengers, bicyclists, and pedestrians; addressing the proper application of micro-simulation analysis and the evaluation of those results; examining active traffic management in relation to both demand and capacity; and exploring specific tools and generalized service volume tables, to assist planners in quickly sizing future facilities"--Transportation Research Board website.